2020
DOI: 10.1080/13102818.2020.1806107
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of the AAAP family in Fragaria vesca

Abstract: The amino acid/auxin permease (AAAP) gene family plays a significant role in the long-distance amino acid transport and is involved in plant stress responses and various developmental processes. The functions of the AAAP family have been extensively discussed in multiple organisms, whereas detailed information of this family in strawberry (Fragaria vesca) has not been reported yet. In this study, we identified 45 AAAP genes in the strawberry genome. Phylogenetic analysis indicated that AAAPs from strawberry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The characteristic motifs for identification of AAT gene family members were PF01490 (Aa_trans) and PF00324 (Aa_permease). Studies published so far have identified a varied number of AAT gene family members such as Arabidopsis (63), rice (85), wheat (296), potato (72), rapeseed (203), soybean (189), strawberry (45), cotton ( Gossypium hirsutum - 190, G. barbadense - 190, G. arboretum - 101, and G. raimondii - 94), tomato (88) and poplar (83) (Rentsch et al 2007 ; Zhao et al 2012 ; Wu et al 2015 ; Cheng et al 2016 ; Ma et al 2016 ; Wan et al 2017 ; Liang et al 2020 ; Tian et al 2020 ; Yang et al 2021 ; Omari 2021 ; Kong et al 2022 ; Du et al 2022 ). In the current study we have identified 84 AAT genes in P. vulgaris which is like rice, tomato and poplar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristic motifs for identification of AAT gene family members were PF01490 (Aa_trans) and PF00324 (Aa_permease). Studies published so far have identified a varied number of AAT gene family members such as Arabidopsis (63), rice (85), wheat (296), potato (72), rapeseed (203), soybean (189), strawberry (45), cotton ( Gossypium hirsutum - 190, G. barbadense - 190, G. arboretum - 101, and G. raimondii - 94), tomato (88) and poplar (83) (Rentsch et al 2007 ; Zhao et al 2012 ; Wu et al 2015 ; Cheng et al 2016 ; Ma et al 2016 ; Wan et al 2017 ; Liang et al 2020 ; Tian et al 2020 ; Yang et al 2021 ; Omari 2021 ; Kong et al 2022 ; Du et al 2022 ). In the current study we have identified 84 AAT genes in P. vulgaris which is like rice, tomato and poplar.…”
Section: Discussionmentioning
confidence: 99%
“…When we investigate the list of species where AATs have been identified show a glaring lack of such studies in legumes. Until now AAT gene family was identified in G. max (Liang et al 2020 ) and the current study adds Phaseolus vulgaris as the second to the list. Research on crucial gene families like AATs holds significance because, as transporters, they may play a vital role in transporting nutrients associated with Biological Nitrogen Fixation (BNF) and mycorrhization..…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…AAAP protein is mainly involved in regulating the long-distance transport of amino acids in the body in plants, mediating amino acid transport across membrane structures, and participating in a variety of other life processes [9]. So far, AAAP genes in several species have been identified, such as Arabidopsis [10], rice [11], moso bamboo [12], Fragaria vesca [13], and Brassica rapa [7] et al The function of many AAAP genes verified in model species. In Arabidopsis thaliana and Oryza sativa, AtAAP1 mediates the amino acid transport in embryo and root cells [14,15]; AtAAP2 could impact the metabolism of seed yield and oil content through the xylem-phloem transfer [16]; AtAAP3 is exclusively expressed in the root involved in amino acid uptake from soil [8] and OsAAP3 could control the yield by influencing the amino acid transfer [17]; AtAAP4 also plays a role in phloem loading [9]; AtAAP5 may perform amino acid import in companion cells in different organs [18,19] and OsAAAP5.…”
Section: Introductionmentioning
confidence: 99%
“…As the two widely studied families of the APC superfamily, the APC family includes the cationic amino acid transporters (CATs), the amino acid/choline transporters (ACTs), and the polyH transporters (PHSs), while the AAAP family contains the amino acid permeases (AAPs), the lysine and histidine transporters (LHTs), the proline transporters (ProTs), the auxin transport protein (AUXs), and the aromatic and neutral amino acid transporters (ANTs). The results of genomic comparative analyses revealed that the amino acid transporters are widely distributed in plants, with increasing evidence clearly demonstrating that the amino acid transporters function in diverse ways [6]. However, the physiological functions of these amino acid transporters remain unclear.…”
Section: Introductionmentioning
confidence: 99%